Kerangka Hukum Pengakuan Agama dan Kepercayaan dalam Kerangka Kebebasan Beragama di Indonesia - Muhammad Adiguna Bimasakti (Badan Pembinaan Ideologi Pancasila, 2025)
The right to adhere to a religion or belief is a fundamental human right recognized globally, including in the Universal Declaration of Human Rights (UDHR). Freedom of religion or belief in Indonesia is guaranteed by the Constitution, specifically in Articles 28E and 29 of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945). As a pluralistic nation rich in spiritual heritage, Indonesia is generally considered to officially recognize only six religions: Islam, Protestantism, Catholicism, Hinduism, Buddhism, and Confucianism. The other religious groups often face legal, social, and administrative challenges, including discrimination and lack of recognition by the state. This study employs a normative juridical approach, using secondary data from legislation and court decisions. The paper aims to examine the constitutional guarantees and practical implementation of religious freedom in Indonesia, the legal and social challenges faced, and the complexities of national policies in relation to Indonesia's commitment to implementing the International Covenant on Civil and Political Rights (ICCPR). The findings show that although the Constitution guarantees religious freedom, its implementation remains discriminatory toward followers of traditional beliefs. Therefore, policy reform and harmonization of national regulations with international human rights principles and Pancasila values are necessary to create inclusive legal protections. By critically examining existing policies in Indonesia and their social contexts, this paper offers recommendations for the development of an ideal policy framework that can protect human rights, particularly regarding religious freedom.